Prevalence and factors associated with suicidal ideation and attempts among mentally ill patients in the psychiatry OPD at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia - Awol Dawud Mohammed; Takele Menna; Mohammed Ayalew; Tesfalem Teshome; Mikiyas Alayu; Neamin Tesfay (Frontiers Media S.A., 2024)
BackgroundEvery year, more than 800,000 people die due to suicide (one person every 40 s), ranking as the second leading cause of death next to traffic accidents in individuals aged 15-29 years. The objective of this study was to assess the prevalence and factors associated with suicidal ideation and attempts among mentally ill patients.MethodAn institutional-based, cross-sectional study was conducted between December 2019 and January 2020. Data were collected using a convenient sampling technique until the required sample size was achieved. The total sample size was 385. The Suicidal Behavior Questionnaire-Revised (SBQ-R), Oslo Social Support Scale, and self-prepared to assess suicide were used. Data collection was carried out by psychiatry professionals through face-to face interviews. Data were analyzed, and bivariate and multivariable logistic regression analyses were conducted using Statistical Package for the Social Sciences (SPSS) version 23.ResultA total of 385 patients participated in the study. Of these, 216 (56%) were men. The prevalence of suicide ideation was 255 (66.2%). The odds of suicidal ideation and attempt was almost three times higher [adjusted odds ratio (AOR) = 2.79, 95% confidence interval (CI) 1.11-6.98]; among patients who felt hopeless, the OR was around two times higher (AOR = 2.44, 95% CI 1.17-5.08); among patients who had a family history of suicide, the OR was almost three times higher (AOR = 2.56, 95% CI 1.00-6.53); among patients who stopped their medication, the OR was approximately two times higher (AOR = 2.25, 95% CI 1.14-4.46); the OR of suicidal ideation and attempts was almost six and four times higher (AOR = 5.86, 95% CI 1.30-26.41; and AOR = 3.61, 95% CI 1.01-12.88) among patients who were educated to primary and secondary level, respectively.ConclusionIn this study, carried out in Ethiopia, suicidal ideation and attempts were more common among men than women. The prevalence of suicidal ideation and attempts showed a significant public health issue among hospital-attending and chronic mentally ill adolescents, which requires a large emphasis. We recommend that suicide prevention needs to involve non-governmental and non-profit organizations, universities, and civil society at different levels.